(untitled) (Malay Literature, 2021)
Humans communicate by using verbal mediums such as speech and writing. The purpose of communication is to spread the information, thoughts, feelings and an individual’s emotions. Communication is vitally important in human life because without communication, we as human beings are unable to exchange or share views, information, thoughts, feelings and emotions. It is for this reason that humans communicate with each other. Communication is divided into two forms namely, verbal or non-verbal. Verbal communication is oral, while non-verbal communication includes written language, sign language, drawings, kinesics, chronemics, paralinguistics and proxemics. In the context of this study, the display of emotional elements in Malay manuscripts is a form of human communication through the characters in these manuscripts. Because of that, this study will focus on the display of emotional elements in the form of kinesics as the non-verbal communication of characters in old Malay manuscripts. This study employs the data analysis method, in analysing the content of old Malay manuscripts such as Hikayat Putera Jayapati and Hikayat Si Miskin. Other than that, this study will use Arnold-Ellis’s Cognitive Theory to strengthen the argument of the study. The results of the study found that between the emotional kinesics elements are eye gestures, facial expressions, touch, limb movements and out-of-control behaviours. Thus, this study proves that humans communicate with each other through the expressions of emotions and behaviours as displayed by the characters featured in the Malay manuscripts. Keywords: Non-verbal, emotions, kinesics, communication, Malay manuscripts